Insights into the role of community participation as a tool for local support: a normative model for competitive and sustainable destination development - Iqbal, Aatif; Ramachandran, Sridar; May Ling, Siow; Subramaniam, Thanam; Latiff, Khairunnisak (Human Resource Management Academic Research Society, 2023)
Community participation as an efficient tool for gaining local residents' support for the development of sustainable and competitive tourist destinations has been adequately established in the tourism discourse. However, due to the dynamic nature of the industry and the associated complexities involved, the conceptualization in terms of theory and operationalization of the notion concerning practicalities is still debated. Given that the wrong conceptualization of the phenomenon could lead to wrong operationalization which would translate into unwanted consequences both for the destination developers and destination communities, the issue cannot be ignored. To address the issue, this study proposes a normative model of community participation with an aim to put some of these complexities in a clear perspective. By employing Tosun`s typology, it is argued that community participation in tourism planning and decision-making, operationalization and management, and benefit receiving takes place at different levels based on the degree of control and authority that local residents have over the tourism development process. To ensure meaningful participation in all the major stages of the developmental process, local communities need to be adequately empowered. A high level of empowerment would ensure spontaneous participation which is the most desired level of participation. On the contrary, a lower level of empowerment would result in coercive participation with the least control and benefits reaching the local communities. It would ultimately lead to antagonization and a lack of local support for any destination development strategies that the developers adopt for sustainable and competitive tourism in the locality.